Cuistow: Chinese Unique Inlay Bristow. (6th January 2021) - Lin, Lin; Zhang, Min; Song, Qingfa; Cheng, Xu; Shao, Zhenxing; Yan, Hui; Cui, Guoqing
Abstract : Background: The prevalence of nonunion after the Latarjet procedure remains high. The purpose of the present study was to investigate healing and clinical outcomes after a novel arthroscopic coracoid process transfer procedure. Methods: Sixty-three patients who underwent the arthroscopic inlay Bristow procedure combined with Bankart repair were identified, and 51 patients who met the inclusion criteria were enrolled in this study. The key feature of this technique was that the coracoid process was trimmed and fixed into a trough (5 to 10 mm deep) in the glenoid neck with a metal screw. Bone graft union and positioning accuracy were assessed with use of postoperative computed tomography (CT) imaging. Clinical examinations, return to sport, and functional scores (American Shoulder and Elbow Surgeons [ASES] and Rowe scores) were recorded. Results: The mean duration of follow-up (and standard deviation) was 41.5 ± 7.7 months (range, 36 to 48 months). Postoperative CT scans showed that the position of coracoid graft was at 4:10 (from 3:50 to 5:00) (referencing the right shoulder) in the sagittal view. The α angle was 16.4° ± 9.5°, with 4 (7.8%) of 51 screws being over-angulated (α > 25°). On the axial view, the graft position was considered to be flush in 33 patients (64.7%), medial in 11 (21.6%), congruent in 7 (13.7%), and lateral or too medial in none. At 1 year, the coracoid graft had healed in 49 patients (96.1%) and had failed to unite in 2 patients. CT scanning, performed for 47 patients, showed grade-0 osteolysis in 9 patients, grade-1 osteolysis in 21 patients, and grade-2 osteolysis in 17 patients. At the time of the latest follow-up, there was a significant increase in the Rowe score (from 35.5 ± 8.3 to 95.7 ± 7.2) and the ASES score (from 71.2 ± 9.7 to 91.5 ± 4.4), and 87.0% of patients were able to return to sport. No arthropathy was observed in any patient. Conclusions: After a minimum 3-year follow-up, the arthroscopic inlay Bristow procedure resulted in a high rate of graft healing, excellent clinical outcomes, and a high rate of return to sports. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.